The Ups and Downs of Daily Life During COVID-19: Age Differences in Affect, Stress, and Positive Events. (17th July 2020) - Klaiber, Patrick; Wen, Jin H; DeLongis, Anita; Sin, Nancy L
Abstract: Objectives: Past research has linked older age with greater emotional well-being and decreased reactivity to stressors, but it is unknown whether age-related advantages in emotional well-being are maintained in the wake of COVID-19. We examined age differences in exposure and affective reactivity to daily stressors and positive events in the first several weeks of the COVID-19 outbreak. Methods: In March and April 2020, 776 adults from Canada and the United States aged 18–91 (mean age 45) years reported COVID-19 threats at baseline, then completed nightly surveys for 1 week about their daily stressors, positive events, and affect. Results: Younger age predicted more concerns about the threat of COVID-19 across multiple domains, in addition to lower positive affect, higher negative affect, and less frequent positive events. Younger adults had more non-COVID-19 daily stressors and higher perceived control over stressors, but lower perceived coping efficacy than older adults. There were no age differences in the frequency of COVID-19 daily stressors nor perceived stressor severity. Younger adults had greater reductions in negative affect on days when more positive events occurred and greater increases in negative affect on days when non-COVID-19 stressors occurred. Age moderation was attenuated for negative affective reactivity to COVID-19 stressors. Age did not moderate positive affective reactivity to daily events. Discussion: In the early weeks of the pandemic, older adults showed better emotional well-being and less reactivity to stressors but did not differ from younger adults in their exposure to COVID-19 stressors. Additionally, younger adults benefited more from positive events.